Survey of the perceptions of health practitioners regarding Functional Neurological Disorders in Australia. (September 2019) - Lehn, Alexander; Bullock-Saxton, Joanne; Newcombe, Peter; Carson, Alan; Stone, Jon
Highlights: Functional Neurological Disorders are common and cause major disability. Modern treatments can lead to dramatically improved outcomes. Self-perceived knowledge among health professionals in Australia about FNDs is poor. Health professionals in Australia can be uncomfortable discussing FND with patients. Better education and teaching about FND could improve patient care. Abstract: Objectives of this study were to identify the knowledge and support needs for a wide range of health professions who come in contact with patients with Functional Neurological Disorders (FND) in Australia. Invitations to an anonymous online survey (36 items) were sent to health professionals (practicing in the fields of neurology, psychiatry, psychology, general practice, nursing and physiotherapy) who are involved in the care of patients suffering from FND. Potential participants were invited via professional and hospital databases, advertising in professional newsletters as well as direct emails. A total of 538 health professionals completed the questionnaire. Most participants did not feel well educated about FND with only 14% of General practitioners (GPs) reporting 'good' knowledge. Neurologists, GPs and nurses reported lower clinical interest and greater negative attitude towards FND than psychiatrists, psychologists and physiotherapists. Many health professionals do not feel confident discussing the possibility of a Functional Neurological Disorder with a patient. Seeing more patients per year was significantly correlated with greater knowledge (r = 0.54) and confidence diagnosing (r = 0.49) FND. It was also significantly related to confidence in discussing the diagnosis of FND with a patient (r = 0.44). These factors were not significantly related to years of practice. Although patients suffering from Functional Neurological Disorders are commonly seen by many health professionals in clinic practice, there is little training in this area and self-perceived knowledge in Australia is generally poor. There is, however, clear interest in this area and our findings suggest that improved teaching and education of health professionals about FND and its management could potentially have a significant impact towards better patient care.